Synthesis and characterisation of a novel Y-shaped liquid crystalline epoxy and its effect on isotropic epoxy resin. Issue 10 (9th August 2019) - Lin, Zirui; Cong, Yuehua; Zhang, Baoyan; Huang, Haozhou
ABSTRACT: A novel Y-shaped liquid crystalline epoxy with a rigid core with three flexible liquid crystalline arms (ETTPM) was synthesised and its structure was characterised by Fourier transform infrared spectroscopy and nuclear magnetic resonance (NMR) spectroscopy. It was analysed and observed by differential scanning calorimetry, X-ray diffraction and polarised optical microscopy (POM) that the liquid crystal phase was stable on the temperature range of 107.8°C. In particular, an unusual transition phenomenon of liquid crystal phases was observed. Modified epoxy-resin-cured products were prepared using ETTPM, epoxy resin E51 and 4, 4-diaminodiphenyl methane. The liquid crystalline domains in cured products were observed by researching their scattering effect on laser. Mechanical tests showed that ETTPM was effective for the mechanical properties improvement of epoxy-resin-cured products, as demonstrated in the improvement of impact strength, tensile strength and tensile elasticity modulus. The impact fracture cross-sections and surface morphologies were studied further by POM and scanning electron microscopy (SEM). Crack deformation, crack split and notable plastic deformations were found in modified epoxy-resin-cured products, and these factors played important roles in improving the impact strength. Graphical Abstract: